1986
DOI: 10.1203/00006450-198601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Isovaleryl-CoA Dehydrogenase Activity in Isovaleric Acidemia Fibroblasts Using an Improved Tritium Release Assay

Abstract: ABSTRAm. Isovaleric acidemia is a disorder of leucine metabolism caused by a deficiency of isovaleryl-CoA dehydrogenase. At least two clinical subgroups of patients exist: a severe form, in which symptoms occur within the 1st wk of life, and a milder variant in which manifestations develop later in life. We developed a modified version of the tritium release assay to accurately measure residual isovaleryl-CoA dehydrogenase activity in fibroblasts from patients with both forms of isovaleric acidemia. In the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
(7 reference statements)
0
11
0
1
Order By: Relevance
“…Fibroblasts, lymphocytes, and amniocytes all have measurable amounts of IVD activity and serve as ready sources of tissue for this purpose [Ensenauer et al, 2004;Kleij et al, 1995;Mohsen et al, 1998;Vockley et al, 1991]. While significant residual activity blunts the level of abnormal metabolites, correlation between clinical presentation and enzyme activity has been poor [Hyman and Tanaka, 1986;Ikeda et al, 1985b;Vockley et al, 1991].…”
Section: Biochemical Diagonosis and Follow Upmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblasts, lymphocytes, and amniocytes all have measurable amounts of IVD activity and serve as ready sources of tissue for this purpose [Ensenauer et al, 2004;Kleij et al, 1995;Mohsen et al, 1998;Vockley et al, 1991]. While significant residual activity blunts the level of abnormal metabolites, correlation between clinical presentation and enzyme activity has been poor [Hyman and Tanaka, 1986;Ikeda et al, 1985b;Vockley et al, 1991].…”
Section: Biochemical Diagonosis and Follow Upmentioning
confidence: 99%
“…Several direct and indirect methods to assay IVD activity have been published and, in addition to molecular genetic analysis, can be used to confirm a diagnosis of IVA [Hyman and Tanaka, 1986;Mohsen et al, 1998;Rhead and Tanaka, 1980;Shih et al, 1973;Tajima et al, 2005;Vockley et al, 1991;Yoshida et al, 1985]. Fibroblasts, lymphocytes, and amniocytes all have measurable amounts of IVD activity and serve as ready sources of tissue for this purpose [Ensenauer et al, 2004;Kleij et al, 1995;Mohsen et al, 1998;Vockley et al, 1991].…”
Section: Biochemical Diagonosis and Follow Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Dubiel et al (23) also found no difference in the residual activity of 12 isovaleric acidemia cell lines using macromolecular-labeling techniques. An improved tritium release assay using an acyl-CoA dehydrogenase inhibitor (methylenecyclopropylacetyl-CoA) (24) gave an unexpected finding. The acute, early-onset form had residual activity of 0.41 pmol 3H20/min/mg protein compared to a normal of 19.4 + 8.0 whereas three milder clinical forms had no enzyme activity.…”
Section: Iva Isovaleric Acid Ivg Isovalerylglycine Msud Maple Syrumentioning
confidence: 99%
“…The acute, early-onset form had residual activity of 0.41 pmol 3H20/min/mg protein compared to a normal of 19.4 + 8.0 whereas three milder clinical forms had no enzyme activity. The authors suggested that age of onset and the severity of clinical presentation were not caused by differences in impaired isovaleryl-CoA dehydrogenase, but by the competency of the glycine-N-acylase pathway to use accumulated isovaleric acid (24). When [2][3][4][5][6][7][8][9][10][11][12][13][14]C-leucine conversion to I4CO2 by intact cells was used as the enzyme assay, less than 2% residual activity was seen in acute isovaleric acidemia (25).…”
Section: Iva Isovaleric Acid Ivg Isovalerylglycine Msud Maple Syrumentioning
confidence: 99%